2002
DOI: 10.1007/s002340100660
|View full text |Cite
|
Sign up to set email alerts
|

Sequential MRI and MR spectroscopy in embolized meningiomas: correlation with surgical and histopathological findings

Abstract: The preoperative embolization of meningiomas is commonly used to facilitate surgery. The purpose of this study was to evaluate the morphological and metabolic changes in embolized meningiomas and to correlate the results with surgical and histopathological findings. In a prospective study, 36 patients with intracranial meningiomas were included. The extent of devascularization was assessed by angiography and MR volumetry. MRI and MR spectroscopy (MRS) were performed before and sequentially after embolization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 5 publications
(8 reference statements)
0
6
0
1
Order By: Relevance
“…These findings are in accordance with those of previous studies in which MR spectroscopy had been applied to studying GC. 1,30 The elevated Cho level is related to cellular proliferation and the reduced NAA concentration corresponds to reversible neuronal injury and/or focal invasion by the tumor process. At a long echo time, Cho levels were more elevated in patients harboring LGGs than in those with GC.…”
Section: Metabolic Patterns Of Gc and Lggmentioning
confidence: 99%
“…These findings are in accordance with those of previous studies in which MR spectroscopy had been applied to studying GC. 1,30 The elevated Cho level is related to cellular proliferation and the reduced NAA concentration corresponds to reversible neuronal injury and/or focal invasion by the tumor process. At a long echo time, Cho levels were more elevated in patients harboring LGGs than in those with GC.…”
Section: Metabolic Patterns Of Gc and Lggmentioning
confidence: 99%
“…Microsurgical removal is reported to be facilitated by improved intraoperative hemostasis [13]. Moreover, tumor softening due to necrosis has been observed after a period of time which ameliorated tumor resection [5]. In a selected group of patients (i.e., old patients with an increased surgical risk, or patients with multiple meningiomas), embolization without subsequent surgery has been suggested as palliative treatment to cause tumor shrinkage and to relieve the mass effect [2,3,21].…”
Section: Introductionmentioning
confidence: 99%
“…55 Comparing T1 post-gadolinium imaging to dynamic MR using a contrast bolus indicates that following embolization some areas of embolized tumor may enhance in a delayed fashion owing to slow collateral flow ( Figure 17). 56 On the basis of MR findings it has been suggested that MRI and MRS following embolization may serve a purpose to identify revascularization and establish the presence of fatty degeneration of the meningioma. The spectroscopic data indicate high concentrations of lactate at 24 h after embolization, followed by broad aliphatic signal several days later.…”
Section: Imaging Meningiomas Postembolizationmentioning
confidence: 99%